1995
DOI: 10.1007/bf00123374
|View full text |Cite
|
Sign up to set email alerts
|

Poisson's ratio of glass-polyalkenoate (?glass-ionomer?) cements determined by an ultrasonic pulse method

Abstract: Poisson's ratio has been determined for four glass-polyalkenoate cements; one experimental luting type, one experimental restorative type, one commercial restorative type (Chelon-Fil, ex. ESPE GmbH) and one cermet-reinforced cement EChelon-Silver, also ex. ESPE]. An ultrasonic pulse method was employed for the Poisson's ratio determinations. For the restorative materials, including the cermet-reinforced cement, the values obtained were all in the region of 0.3. For the luting cement, on the other hand, the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…The value of K IC is affected by three properties, these being Young's modulus (E), the Critical Strain Energy Release Rate (G IC ) and Poisson's ratio ( ) through the relationship: K IC = [G IC E/(1 − 2 )] 0.5 . For GIs the value of Poisson's ratio, measured by the ultrasound method (which is appropriate for the research reported in this paper) is in the region of 0.3 for products intended for use as restoratives but increases to 0.35 for luting cement products [46]. The greater water content to produce the necessary flow properties for a luting cement is the reason for the increase in Poisson's ratio [46].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The value of K IC is affected by three properties, these being Young's modulus (E), the Critical Strain Energy Release Rate (G IC ) and Poisson's ratio ( ) through the relationship: K IC = [G IC E/(1 − 2 )] 0.5 . For GIs the value of Poisson's ratio, measured by the ultrasound method (which is appropriate for the research reported in this paper) is in the region of 0.3 for products intended for use as restoratives but increases to 0.35 for luting cement products [46]. The greater water content to produce the necessary flow properties for a luting cement is the reason for the increase in Poisson's ratio [46].…”
Section: Discussionmentioning
confidence: 95%
“…For GIs the value of Poisson's ratio, measured by the ultrasound method (which is appropriate for the research reported in this paper) is in the region of 0.3 for products intended for use as restoratives but increases to 0.35 for luting cement products [46]. The greater water content to produce the necessary flow properties for a luting cement is the reason for the increase in Poisson's ratio [46]. Whereas this variation is relevant to all the materials in the present research, in practice the effect of the change is minimal [(1 − 2 ) −0.5 is 1.05 for = 0.3 and 1.06 for = 0.35] and can be disregarded in this discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where a was the radius of the knife-edge support (10 mm) and v was Poisson's ratio (0.3 for GI restoratives 31 ). The thickness of each fractured fragment was measured at the point of fracture using the micrometre and the mean thickness h was determined.…”
Section: Bfsmentioning
confidence: 99%
“…The BFS tests were performed with a universal testing machine (Digimess MX5000) at a crosshead speed of 1 mm/min, using a 4 mm diameter ball indenter, loading the specimens centrally. The BFS value was calculated according to the following equation [17]: BFS = P / h 2 ((1 + v )(0.485ln⁡( a / h ) + 0.52) + 0.48), where P is the load at fracture, a is the radius of the support (5 mm), v is the Poisson ratio (0.3 for glass-ionomer restorative cements) [18], and h represents the thickness of the specimen, obtained by the mean thickness value of the two remaining fragments of each disc that is fractured when loaded.…”
Section: Methodsmentioning
confidence: 99%